Law for the layman - Arora, Manish (New Delhi, 2013)
Law is the comment of society and essential medium of change in understanding social values. Law is the proper reasoning of what is good and useful to the society and what is not good or is harmful to any individual or to a group of people or to society and accordingly, certain rules are framed. State, in order to maintain peace and order in the society, formulates rules of conduct to be followed by the people. These sets of rules and regulations of human conduct are called "Law".
Keywords: Law